2015
DOI: 10.1016/j.cell.2015.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Cpf1 Is a Single RNA-Guided Endonuclease of a Class 2 CRISPR-Cas System

Abstract: The microbial adaptive immune system CRISPR mediates defense against foreign genetic elements through two classes of RNA-guided nuclease effectors. Class 1 effectors utilize multi-protein complexes, whereas Class 2 effectors rely on single-component effector proteins such as the well-characterized Cas9. Here we report characterization of Cpf1, a putative Class 2 CRISPR effector. We demonstrate that Cpf1 mediates robust DNA interference with features distinct from Cas9. Cpf1 is a single RNA-guided endonuclease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

95
4,133
8
29

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,900 publications
(4,265 citation statements)
references
References 49 publications
95
4,133
8
29
Order By: Relevance
“…More studies on improving the fidelity and finding an alternative have been reported 1, 3, 4. To broaden the applicability of our delivery system, we explored other gene editing alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…More studies on improving the fidelity and finding an alternative have been reported 1, 3, 4. To broaden the applicability of our delivery system, we explored other gene editing alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…Both crRNA and tracrRNA are required for Cas9‐mediated targeting. In contrast, a single ~44‐nucleotide (nt) crRNA with a 5′‐located direct repeat sequence and a spacer sequence that complements the target are sufficient to guide the DNA cleavage of Cpf1 (Zetsche et al ., 2015). Moreover, Cpf1 recognizes the thymidine‐rich protospacer‐adjacent motif (PAM) and makes staggered cuts distal to the PAM site (Fonfara et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Cas9, only three families of class 2 Cas effector proteins have been discovered and experimentally validated: Cpf1, C2c1, and C2c2 4,24,25 . Another gene, c2c3, which was identified only on small DNA fragments, has been suggested to also encode such a protein 4 .…”
mentioning
confidence: 99%